Hepatic F-box Only Protein 2 (FBXO2) Might Not Mediate Glucose Homeostasis in Obese Diabetic Mice. (29th May 2020) - Wong, Siau Yen; Lu, Peiran; Wu, Lei; Montgomery, Mckale; Chowanadisai, Winyoo; Lucas, Edralin; Smith, Brenda; Clarke, Stephen; Lin, Dingbo
Abstract: Objectives: F-box only protein 2 (FBXO2) is an E3 ubiquitin protein ligase highly expressed in the brain and cochlea, hepatic FBXO2 protein levels are very low in healthy mice. It was reported that hepatic FBXO2 elevation causes hyperglycemia in obese mice. Here, we investigated whether hepatic FBXO2 expression was enhanced in diabetic human samples; and if so, whether deficiency of FBXO2 could improve blood glucose control in diet-induced obese diabetic mice. Methods: Human liver specimen samples from healthy and type 2 diabetic human subjects were subject to transcriptomics and proteomics. The results were confirmed by real-time QPCR and immunoblotting, respectively. Male FBXO2 whole-body knockout (KO) and C57BL/6 J mice (WT, genetic background) at 6 weeks of age were fed a high fat (26% kCal)/high sucrose (15% kCal)/high fructose (15% kCal) diet for 8 weeks. Food intake and body weight gain were monitored weekly. Glucose tolerance and insulin tolerance tests were performed at the 7th week of dietary intervention. At the termination of intervention, mice were euthanized, and blood and liver tissues were collected for further assessment. Primary mouse embryonic fibroblasts (MEF) cells were isolated from WT and KO mice. Mitochondrial superoxide was detected by MitoSOX live cell staining. Results: Transcriptomics and proteomics results showed vast shifts in pathways involved in energy metabolism and mitochondrial function, and significant elevation of FBXO2 expression at mRNA and protein levels in diabetic human livers. However, deficiency of FBXO2 did not alter mitochondrial superoxide production in MEF cells and did not cause an elevation of the fasting blood glucose level before a diet feeding. Moreover, both strains had significantly elevated fasting blood glucose levels after the high-fat diet intervention but did not differ by strains. The insulin sensitivity had no significant difference between strains after diet intervention. Conclusions: The results suggested that FBXO2 depletion did not alter glucose homeostasis in diet-induced obese mouse models, though diabetic humans had a highly elevated hepatic FBXO2 level. Funding Sources: N/A.